2014
DOI: 10.1111/jdv.12484
|View full text |Cite
|
Sign up to set email alerts
|

Triple combination as adjuvant to cryotherapy in the treatment of solar lentigines: investigator‐blinded, randomized clinical trial

Abstract: Triple combination cream can be used to enhance the resolution of solar lentigines, and to significantly reduce melanin levels and lentigines count, improving treatment results. It was well-tolerated and did not increase the occurrence of neither erythema nor other side-effects after the cryotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
0
17
0
8
Order By: Relevance
“…In most patients a single treatment completely removes the spots and healing is fast. With many other treatments such as cryotherapy or other lasers post-inflammatory hyperpigmentation is a challenge [14]. However, post-laser treatment needs sun-/ultraviolet light-protection and a moisturizer [10].…”
Section: Discussionmentioning
confidence: 99%
“…In most patients a single treatment completely removes the spots and healing is fast. With many other treatments such as cryotherapy or other lasers post-inflammatory hyperpigmentation is a challenge [14]. However, post-laser treatment needs sun-/ultraviolet light-protection and a moisturizer [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options of actinic lentigines can be divided into two main categories: photochemical and topical applications of specific actives . Photochemical treatments include cryotherapy, laser, intense pulsed light and chemical peels . Topical application of specific actives aims at inhibition of melanin production, blockage of melanocyte biostimulation and suppression of melanin delivery to final acceptor cells, not without possible side‐effects .…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Although cryotherapy has shown good results, patients complain about discomfort during the treatment and unwanted hypopigmentation as a side effect [3,4]. A recent study by Hexsel et al showed a reduction of these adverse effects by combining the cryotherapy with a triple combination cream [5]. Histologically, there is an increased number of pigment granules in the keratinocytes and the condensed stratum corneum [6].…”
mentioning
confidence: 99%